Influence of Water Immersion on Coal Rocks and Failure Patterns of Underground Coal Pillars Considering Strength Reduction - Haihua Zhu; Peitao Wang; Kewei Zhang; Yijun Gao; Zhenwu Qi; Meifeng Cai (Applied Sciences)
The long-term immersion of coal rock may affect its mechanical properties and failure modes, potentially impacting the stability of coal pillars. This work aims to investigate the influence of the immersion duration on the mechanical properties and fracture evolution processes of coal, employing acoustic emission detection and the digital image correlation (DIC) method. The work focuses on the weakening law of the coal pillar dam in contact with water and obtains a model of the strength deterioration after different periods of water immersion. The stress–strain curves of coal specimens with varying immersion durations are obtained. The results show that the peak absorption rate of coal samples immersed in water transpires within 24 h, with fundamental saturation being achieved at between 25 and 30 days at saturation moisture content of 1.97%. The specimen’s compressive stress after being immersed in water for 7 days is 3.34 MPa, with strain of 0.18%. The cracking stress is 15.60 MPa, with strain of 0.54%. The peak stress is recorded at 27.65 MPa, with strain of 0.92%. The complete rupture stress measures 23.37 MPa, with the maximum strain at 0.95%. During the yielding stage, the specimen has the highest strain increment of 0.38%. Short-term immersion brings about an increase in the coal sample’s plasticity, exhibiting a relatively minor softening impact of water, resulting in comparatively intact fragmentation and modest breakage. A negative exponential function relationship is observed between the compressive strength of coal and the immersion duration. The mechanical reduction relationship is utilized to analyze the failure patterns of coal pillars in underground reservoirs. With prolonged water immersion, the damage area expands to include the coal pillars and the surrounding rock of the excavation area.